SPAIN AND THE HOLY ALLIANCE IN THE PUBLIC DISCOURSE OF THE FIRST MEXICAN EMPIRE (1821-1823) (Tzintzun, Revista de Estudios Históricos, 2024)
In 1820, Rafael del Riego started an uprising in Spain to establish a liberalgovernment in the Spanish Empire. This concluded the Sexenio Absolutista,giving way to the Trienio Liberal. In Europe, the revolutionary spread led Portugal,Naples and Piedmont to follow the same path, seeking to replace their absolutemonarchies with constitutional governments. This would cause the greatEuropean monarchies, allied under the banner of the Holy Alliance, to initiatean interventionist policy to prevent the revolution from crossing their borders.Shortly afterwards, Austria invaded Naples, abolishing its constitutionalgovernment. This article discusses how this interventionist policy was reflectedin the public opinion of the first Mexican Empire (1821-1823). How the possibilityof an alliance between Fernando VII and the coalited monarchic powersimplanted the fear of an imminent Spanish invasion through the Fort of SanJuan de Ulúa, in Veracruz.
Keywords: Holy Alliance; Imperialism; Monarchism; Atlantic Revolutions; Political Imaginaries